2019
DOI: 10.1108/ilt-07-2017-0212
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear stability analysis of micropolar fluid lubricated journal bearings with turbulent effect

Abstract: Purpose The purpose of this paper is to investigate the effect of turbulence on the stability characteristics of finite hydrodynamic journal bearing lubricated with micropolar fluid. Design/methodology/approach The non-dimensional transient Reynolds equation has been solved to obtain the non-dimensional pressure field which in turn used to obtain the load carrying capacity of the bearing. The second-order equations of motion applicable for journal bearing system have been solved using fourth-order Runge–Kutt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Ram et al [74] analysed the effect of turbulent flow on dynamic performance characteristics of journal bearing and found that the stiffness coefficients were decreased in turbulent flow as compared to laminar flow whereas the damping coefficients increased in turbulent flow conditions. It was found that the stability of hydrostatic journal bearing adversely effected due to turbulence [75]. The hole entry journal bearings with constant flow valve and capillary restrictors were analysed and compared with slot entry journal bearings considering micropolar lubrication.…”
Section: Micropolar Lubricantsmentioning
confidence: 99%
“…Ram et al [74] analysed the effect of turbulent flow on dynamic performance characteristics of journal bearing and found that the stiffness coefficients were decreased in turbulent flow as compared to laminar flow whereas the damping coefficients increased in turbulent flow conditions. It was found that the stability of hydrostatic journal bearing adversely effected due to turbulence [75]. The hole entry journal bearings with constant flow valve and capillary restrictors were analysed and compared with slot entry journal bearings considering micropolar lubrication.…”
Section: Micropolar Lubricantsmentioning
confidence: 99%
“…Eringen (1966) reported that micropolar lubrication can improve the performance of the journal bearing system. Das and Guha (2019) revealed in their work that stability can be achieved at N 2 = 0.7 and l m < 20. Nekoeimehr et al (2013) studied the static performance of different lobed bearings and observed an enhancement in their performance for higher lobed bearing.…”
Section: Introductionmentioning
confidence: 96%
“…Feng and Peng (2018) studied the influence of turbulent cavitation flow on the static performance of the thrust bearing with groove texture. Das and Guha (2018) investigated the impact of turbulence on the stability performance of the The current issue and full text archive of this journal is available on Emerald Insight at: https://www.emerald.com/insight/0036-8792.htm bearing micropolar and concluded that turbulent flow has a detrimental impact on stability. Zhu et al (2019) proposed a stochastic turbulent lubrication method, and the performance of bearing with the isotropic rough surface was explored.…”
Section: Introductionmentioning
confidence: 99%
“…Feng and Peng (2018) studied the influence of turbulent cavitation flow on the static performance of the thrust bearing with groove texture. Das and Guha (2018) investigated the impact of turbulence on the stability performance of the bearing micropolar and concluded that turbulent flow has a detrimental impact on stability. Zhu et al.…”
Section: Introductionmentioning
confidence: 99%